Numerical Modelling and Predictive Analysis of Slope Stability Using the Limit Equilibrium Method: A Parametric Study (International Journal of Environmental Sciences, 2023)
Slope instability poses a persistent threat to infrastructure, human settlement, and the natural environment, particularly in rain-intensive regions such as the Indian subcontinent. This study presents a comprehensive numerical investigation of slope stability employing the Limit Equilibrium Method (LEM) as implemented in Rocscience Slide, supported by manual validation using the Ordinary Method of Slices (Fellenius method) in Microsoft Excel. A structured parametric study examines the individual and combined influences of internal friction angle (φ), cohesion (c), unit weight (γ), water table height, and slope inclination on the Factor of Safety (FOS). The software-computed FOS of 1.239 compared favourably with the manually calculated value of 1.060, confirming a theoretically expected conservative deviation of approximately 14% attributable to the neglect of interslice forces in the Fellenius formulation. Parametric results demonstrate that friction angle is the dominant stability parameter for drained granular soils, whilst cohesion governs the stability of undrained cohesive soils. Rising water table height consistently reduces FOS, with full saturation producing the most critical conditions.